Inhibitory Effect of Loranthus parasiticus on IgE-Mediated Allergic Responses in RBL-2H3 Cells - Jae-Myung Yoo; Ju-Hye Yang; Young Soo Kim; Won-Kyung Cho; Jin Yeul Ma (Hindawi Limited, 2016)
The mistletoe Loranthus parasiticus has been used as a compound for traditional medicine in Northeast Asia for a long time and is known to possess neuroprotective action. Nonetheless, the effect of Loranthus parasiticus on allergic responses remains unknown. In the present study, we evaluated whether the water extract of Loranthus parasiticus (LPE) could inhibit IgE-mediated allergic responses in RBL-2H3 cells. LPE inhibited the release of β-hexosaminidase (IC50, 184.5 μg/mL) and the formation of tumor necrosis factor-α (IC50, 84.27 μg/mL), interleukin-4 (IC50, 93.43 μg/mL), prostaglandin E2 (IC50, 84.10 μg/mL), prostaglandin D2, and leukotriene C4 (IC50, 43.27 μg/mL) in a concentration-dependent manner. Moreover, LPE inhibited phosphorylation of Syk, PLCγ1/2, PKCδ, ERK, JNK, p38, and Akt. In the late phase, LPE decreased 5-lipoxygenase phosphorylation and COX-2 expression but not cPLA2 phosphorylation. Additionally, LPE included total phenolic compounds (10.72 mg/g dry weight) and total flavonoids (56.20 mg/g dry weight). These results suggest that the phenolic compounds or flavonoids contained in LPE may be associated with antiallergic activity. The phenolic compounds and flavonoids in LPE are antiallergic phytochemicals capable of inhibiting the activation of the FcεRI signaling cascade in mast cells. Such effects may provide further information for the development of a phytomedicine for allergic diseases.